Laser implantation of niobium and titanium-based particles on hot working tool surfaces for improving the tribological performance within hot stamping - Schirdewahn, Stephan; Spranger, Felix; Hilgenberg, Kai; Merklein, Marion (Defect and Diffusion Forum, 2020)
Within the scope of this work, a laser implantation process has been used, in order to improve the tribological performance of hot stamping tools. This surface engineering technology enables the generation of dome-shaped, elevated and highly wear resistant microfeatures on tool surfaces in consequence of a localized dispersing of hard ceramic particles via pulsed laser radiation. As a result, the topography and material properties of the tool and thus the tribological interactions at the blank-die interface are locally influenced. However, a suitable selection of hard ceramic particles is imperative for generating defect-free surface features with a high share of homogenously disturbed particles. For this purpose, different niobium (NbB2 and NbC) as well as titanium-based (TiB2 and TiC) materials were embedded on hot working tool specimens and subsequently analyzed with regard to their resulting shape and mechanical properties. Afterwards, modified pin-on-disk tests were carried out by using conventional and laser-implanted tool surfaces, in order to evaluate the wear and friction behavior of both tooling systems.<br
CRIS-Team Scopus Importer:2020-11-27
Keywords: Surface modification; Triobology; Laser implantation